Exploring Elicitors of the Beneficial Rhizobacterium Bacillus amyloliquefaciens SQR9 to Induce Plant Systemic Resistance and Their Interactions With Plant Signaling Pathways - Wu, Gengwei; Liu, Yunpeng; Xu, Yu; Zhang, Guishan; Shen, Qirong; Zhang, Ruifu (Molecular plant-microbe interactions, 2018)
Beneficial rhizobacteria have been reported to produce various elicitors that induce plant systemic resistance, but there is little knowledge concerning the relative contribution of multiple elicitors from a single beneficial rhizobacterium on the induced systemic resistance in plants and the interactions of these elicitors with plant signaling pathways. In this study, nine mutants of the plant growth–promoting rhizobacterium Bacillus amyloliquefaciens SQR9 deficient in producing the extracellular compounds, including fengycin, bacillomycin D, surfactin, bacillaene, macrolactin, difficidin, bacilysin, 2,3-butandiol, and exopolysaccharides, were tested for the induction of systemic resistance against Pseudomonas syringae pv. tomato DC3000 and Botrytis cinerea and the transcription of the salicylic acid, jasmonic acid, and ethylene signaling pathways in Arabidopsis. Deficiency in producing any of these compounds in SQR9 significantly weakened the induced plant resistance against these phytopathogens. These SQR9-produced elicitors induced different plant defense genes. For instance, the enhancement of 1,3-glucanase (PR2) by SQR9 was impaired by a deficiency of macrolactin but not surfactin. SQR9 mutants deficient in the lipopeptide and polyketide antibiotics remained only 20% functional for the induction of resistance-related gene transcription. Overall, these elicitors of SQR9 could act synergistically to induce plant systemic resistance against different phytopathogens through different signaling pathway genes, and the bacterial antibiotics are major contributors to the induction.